2013
DOI: 10.1074/jbc.m113.458067
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Activation by Dioxin Targets Phosphoenolpyruvate Carboxykinase (PEPCK) for ADP-ribosylation via 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD)-inducible Poly(ADP-ribose) Polymerase (TiPARP)

Abstract: Background: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD)-activated aryl hydrocarbon receptor (AHR) decreases gluconeogenesis by suppressing phosphoenolpyruvate carboxykinase (PEPCK) transcription via TCDD-inducible poly(ADPribose)-polymerase (TiPARP). Results: AHR enhances PEPCK ADP-ribosylation through TiPARP, and AHR suppression increases ADP-ribosylation PARP-independently. Conclusion: ADP-ribosylation, a new PEPCK posttranslational modification, is subject to complex regulation by the AHR. Significance: AHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Positive effects of PARP-2 on transcription are exerted through facilitating the activity of transcription (co)factors, while negative effects are due to the attraction of cofactors promoting chromatin compaction and the consequent inhibition of transcription (Szá ntó et al, 2014). PARP-7 is a cofactor for aryl-hydrocarbon receptor (Diani-Moore et al, 2013), which suggests its importance combating environmental toxins, PARP-10 interacts with c-Myc (Feijs et al, 2013), while…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects of PARP-2 on transcription are exerted through facilitating the activity of transcription (co)factors, while negative effects are due to the attraction of cofactors promoting chromatin compaction and the consequent inhibition of transcription (Szá ntó et al, 2014). PARP-7 is a cofactor for aryl-hydrocarbon receptor (Diani-Moore et al, 2013), which suggests its importance combating environmental toxins, PARP-10 interacts with c-Myc (Feijs et al, 2013), while…”
Section: Introductionmentioning
confidence: 99%
“…Given that mitochondria are critical components of cellular metabolism, the main sites for energy production, and that many pathophysiological effects linked to TCDD exposure (e.g. diabetes, wasting syndrome, hepatic steatosis, and embryonic development) are related to metabolic pathways, researchers have focused on mitochondrial dysfunction as a potential player in TCDD-induced toxicity (Aly and Domenech, 2009; Angrish et al ., 2011; Carreira et al ., 2015; Diani-Moore et al ., 2010; Diani-Moore et al ., 2013; Forgacs et al ., 2010; Forgacs et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…ARTD14 over-expression reproduces the TCDD effects on glucose metabolism, and it has been suggested that ARTD14 mediates these TCDD effects [178]. TCDD-dependent transcriptional induction of ARTD14 leads to ADP-ribosylation of cytosolic and mitochondrial PEPCKs [180]. However, as AHR suppression also enhances ADP-ribosylation, it is clear that the complex modulatory effects on ADP-ribosylation by AHR are far from being defined at present [180].…”
Section: Artd14mentioning
confidence: 99%